Cat burglar caper - Keene, Carolyn (Keene, Carolyn. Nancy Drew and the clue crew, 2010)
Pete's Pets has adorable new kittens in the shop, but are they stolen and is Nancy Drew's archenemy Deidre Shannon involved? Nancy and her friends investigate when kittens go missing from the River Heights Animal Shelter.